Can the tractor’s cabin allow the noise at the operator’s station? - Marques Filho, Aldir Carpes; Lanças, kléber Pereira (Revista Brasileira de Engenharia de Biossistemas, 2022)
Constant exposure to high noise levels can cause health problems for agricultural machinery operators. Machines equipped with closed cabs can attenuate noise and preserve the operator from an unhealthy condition. Some studies show that in cabin tractors it is possible to renounce the use of hearing protection, however indoor equipment and air conditioning can reach high levels of noise, which need to be further investigated. The present study aimed to evaluate the noise emitted by a cabined agricultural tractor, in different points, inside and outside cabin, in the engine rotations of 800rpm, 2180rpm and 2500rpm. In each reading, 100 noise intensity values were automatically collected, over two minutes with the aid of a digital decibel meter device. The results were compared with the levels assumed by Annex 1 of the regulatory Brazilian standard NR 15, and it was found that the cabin was able to isolate the noise emitted by the engine and its external components in 15%, however, the internal noise reached 81dB(A). The cabin can attenuate external noise and offer a healthy working environment, however, in long working hours it is recommended to use personal protective equipment such as ear protectors.